Neuroprotective effects of quercetin on hippocampal CA1 neurons following middle cerebral artery ischemia‒reperfusion in male rats: a behavioral, biochemical, and histological study - Mehran Mahyar; Erfan Ghadirzadeh; Pedram Nezhadnaderi; Zahrasadat Moayedi; Parniyan Maboud; Arvin Ebrahimi; Ali Siahposht-Khachaki; Narges Karimi (BMC Neurology)
Abstract Introduction Cerebral ischemic strokes cause brain damage, primarily through inflammatory factors. One of the regions most affected by middle cerebral artery occlusion (MCAO) is the hippocampus, specifically the CA1 area, which is highly susceptible to ischemia. Previous studies have demonstrated the anti-inflammatory properties of quercetin. Therefore, this study aimed to investigate the neuroprotective effects of quercetin on hippocampal CA1 neurons following MCAO. Materials and methods Fifty-six male Albino Wistar rats were divided into seven groups (intact, sham, stroke, vehicle, and three quercetin-treated groups receiving 5, 10, and 20 mg/kg, respectively), each containing 8 rats. Various assessments, including brain water content, the rotarod test, the Bederson neurological score, the Morris water maze (MWM) test, the shuttle box test, histopathological evaluations, and measurements of interleukin-10 (IL-10) and interleukin-1β (IL-1β) levels, were conducted across the groups. Results Compared with control rats, 5 and 10 mg/kg quercetin-treated rats presented significant improvements in brain water content, neurological function, and motor function and improved performance in the MWM and shuttle box tests. Histopathological analyses revealed better preservation of CA1 neurons in these groups. Additionally, IL-10 levels significantly increased, whereas IL-1β levels significantly decreased. However, the group receiving 20 mg/kg quercetin showed no statistically significant changes in the parameters assessed (P > 0.05). Conclusion Quercetin may help prevent or ameliorate brain injuries caused by acute stroke, suggesting its neuroprotective effects. The reduction in IL-1β and increase in IL-10 may play key roles in quercetin’s protective mechanism.